Hubungan Kecerdasan Emosional dengan Tingkat Empati dan Kecemasan Pada Mahasiswa Fakultas Kedokteran Universitas Tanjungpura Angkatan 2020 - Sihombing, Jessica Juniarta; Armyanti, Ita; Triharja, Agustina Arundina (Faculty of Medicine, Universitas Andalas, 2023)
Objective: To know the relationship between emotional intelligence and the level of empathy and anxiety among students of Faculty of Medicine in Tanjungpura University, year 2020. Methods: The research design carried out was a cross-sectional analytic study. The study population included students of Faculty of Medicine in Tanjungpura University, year 2020. The sample was taken using a total sampling technique with a total sample of 203 people. Data was obtained from filling in personal data, L-MMPI questionnaire, stressor sheet, emotional intelligence, JSE S-Version, JSE HPS-Version, and BAI. Spearman correlation test was used for the hypothesis test. Results: Hypothesis test results in relation with empathy: self-awareness (p = 0.050), self-control (p = 0.109), self-motivation (p = 0.000), social awareness (p = 0.039), and social skills (p = 0.025). Hypothesis test results in relation with anxiety: self-awareness (p = 0,000), self-control (p = 0.013), self-motivation (p = 0.013), social awareness (p = 0.006), and social skills (p = 0.000). Conclusion: There are significant positive relationship between self-awareness, self-motivation, social awareness, and social skills on levels of empathy; and significant negative relationship between self-awareness, self-control, self-motivation, social awareness, and social skills on levels of anxiety.